Antisemitic and Islamophobic hate speech precedes a decrease in lexico-semantic diversity in comment threads online - Z. P. Rosen; Rick Dale (Humanities & Social Sciences Communications)
Abstract Studies of Antisemitic and Islamophobic hate speech (AHS and IHS) demonstrate that they severely impact the psychological and social well-being of Jewish and Muslim communities. However, work to date has not adequately addressed the effect that the introduction of AHS/IHS has on subsequent expression in groups that tolerate hate speech online. We thus do not know how influential AHS and IHS are. The current study attempts to address this gap in the literature directly by providing an information-theoretic account of what happens when social media users on the website Reddit vary the intensity of Islamophobic and/or Antisemitic sentiment in their comments. We find that the more overtly Antisemitic or Islamophobic the comment, the easier it is to recover the ideas expressed in that comment from subsequent comments. In other words, comments that rank high for AHS or IHS appear to impose a strong bottleneck on the lexico-semantic diversity of subsequent conversations. This effect was strengthened after the onset of the conflict in Gaza and Israel on October 7th, 2023. Our results offer a step toward investigating how information transmission is altered due to the effects of particular kinds of HS, and have direct implications for organizations with a vested interest in content moderation.